2017
DOI: 10.1039/c7cp02734f
|View full text |Cite
|
Sign up to set email alerts
|

Salt-induced thermochromism of a conjugated polyelectrolyte

Abstract: We report here the photophysical properties of a water-soluble conjugated polythiophene with cationic side-chains. When dissolved in aqueous buffer solution (PBS, phosphate buffered saline), there is ordering of the polymer chains due to the presence of the salts, in contrast to pure water, where a random-coil conformation is adopted at room temperature. The ordering leads to a pronounced colour change of the solution (the absorption maximum shifts from 400 nm to 525 nm). Combining resonance Raman spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
29
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 82 publications
6
29
2
Order By: Relevance
“…Intermolecular delocalization leads to formation of narrow energy bands, which increases the number of available end states and homogeneously broadens transition for charges and excitons . This effect has been observed a number of times in organic semiconductors, and it should not be confused with inhomogeneous broadening due to disorder . We note that electron delocalization into fullerene aggregates plays an important role in the functioning of organic solar cells, ,, highlighting the importance of evaluating this parameter via the shape of the C 60 anion band.…”
mentioning
confidence: 71%
“…Intermolecular delocalization leads to formation of narrow energy bands, which increases the number of available end states and homogeneously broadens transition for charges and excitons . This effect has been observed a number of times in organic semiconductors, and it should not be confused with inhomogeneous broadening due to disorder . We note that electron delocalization into fullerene aggregates plays an important role in the functioning of organic solar cells, ,, highlighting the importance of evaluating this parameter via the shape of the C 60 anion band.…”
mentioning
confidence: 71%
“…Attempts to design a better aqueous formulation have thus far focused on tailoring the polyelectrolyte scaffold, through variation of the charge moieties, chain stiffness, and concentration of the polyelectrolyte, , which have shown that the nature of the scaffold proves crucial not just for the resulting PEDOT:PSS structure, but also in the level of doping and stabilization of the PEDOT. ,,, An alternative to the dispersion polymerization approach has relied on making the electronically or optically active component intrinsically water-soluble by the use of conjugated polyelectrolytes (CPEs), which combine a π-conjugated polymer backbone with pendant ionic groups . This approach leads to better tunability over the solution structures, film morphologies, and resulting optoelectronic properties by using a single-component material …”
mentioning
confidence: 99%
“…These differences in the steady-state spectra of polymeric assemblies are commonly analyzed within an HJ-aggregate model 3234 . Owing to the comparable intrachain and interchain couplings, subtle changes in the morphology of the crystalline phase of P3HT have been shown to be able to induce alternatively H-like or J-like dominant character of the spectra 33 .…”
Section: Resultsmentioning
confidence: 99%
“…As detailed in previous studies 36,39 , in TF samples any SE contribution is usually mostly or completely overcome by the PA signal, especially for excitation with short-wavelength/high-photon-energy pump pulses, and residual SE has been mainly attributed to singlet exciton emission from the amorphous regions 49 . A note should be done for the 0-0 SE transition (at around 670 nm) which decreases in the TF sample (H-like) not just because of the higher PA signal but also due to the decreased oscillator strength of the transition 34 .…”
Section: Resultsmentioning
confidence: 99%